Ngô Sĩ Liên’s View in Đại Việt Sử Ký Toàn Thư: Resistance to China or Expression of Equivalence? - Insun Yu, (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
This paper discusses Ngô Sĩ Liên’s resistant attitude against China as implicated in his book, Đại Việt sử ký toàn thư presented to Lê Thánh Tông in 1479. In this book, Ngô Sĩ Liên emphasizes the independent status of Vietnam, particularly rejecting the recognition that China was the ruler of Vietnam between 1407- 1427 by evaluating the Vietnamese resistance during the period known as Thời kỳ Bắc thuộc when China exerted control over Vietnam. He also underscored that a sense of equality existed between Vietnam and China, arguing Vietnam was a different type of civilized country from China. Such a resistant attitude was still observed in the nineteenth century. For instance, emperor Minh Mạng changed the name of the country Việt Nam to “Đại Nam” in 1838. He did so in the counter-psychology to the Qing calling itself “Great Qing”.Received 5th September 2023; Revised 30th September 2023; Accepted 5th October 2023